Fostering Today What is Needed Tomorrow: Investigating Students' Interest in Science. Issue 2 (7th December 2015) - BLANKENBURG, JANET SUSAN; HÖFFLER, TIM NICLAS; PARCHMANN, ILKA
ABSTRACT: This paper investigates the structure of German sixth‐grade students' interest in science ( N = 474; age 11–12 years) by considering different subject‐related contexts (biology, chemistry, and physics) and different activities. Confirmatory factor analysis models were designed to validate the hypothetical structure of interest, connecting the whole spectrum of early school science with Holland's RIASEC model, and revealed that students' interest in science is best described by a cross‐classified model with latent context and activity factors. Students were most interested in investigative and hands‐on activities in all contexts. Despite the young age group, there were significant gender differences with regard to interest in contexts and interest in activities. For example, girls were more interested in artistic and realistic activities among most contexts and generally in the biological context. Surprisingly, boys were more interested in social physics activities than girls. This paper discusses implications for future research, for school science curricula as well as for how to engage students in science with particular emphasis on gender differences.